Static and dynamic characteristics of an hydrodynamic journal bearing - Parkins, D. W. (Cranfield University, 1976)
Hydrodynamic oil film bearings exhibit lateral flexibility which influences the dynamics of rotors they support. This lateral flexibility is specified by coefficients which relate forces generated by the oil film to the instantaneous journal centre velocity and its displacement from an equilibrium position. Previous investigators adopted a linear treatment by taking uniform viscosity with small displacement and velocity increments. Relatively large journal centre velocities are possible in rotating machinery. Therefore, this thesis investigates the non-linear behaviour of these oil film coefficients. Coefficient calculations allowed viscosity to vary with temperature and pressure rendering the governing Reynolds Equation non-linear. A range of positive and negative displacement and velocity increments were examined. Novel experimental techniques have been developed which allow determination of coefficient variation with respective displacement and velocity. Coefficients were deduced from specially chosen, imposed vibration orbits arising from two mutually perpendicular external oscillating forces of variable relative magnitude and phase. Journal centre displacement and velocity were measured using high speed data logging equipment. A unique feature was the ability to obtain, experimental displacement coefficients from the results of both dynamic and incremental loading. It was found necessary to establish the bearing centre separately for each warm-up/load combination. Journal clearance in the hot rotating condition could not be measured to the precision required by its sensitivity to calculated load. Clearance and cavitation zone pressures were deduced from simultaneous predictions of the measured vertical load and attitude angle. Theoretical oil film tensile forces were necessary, a proposition supported by recently published experimental findings. Theoretical results for an equivalent uniform viscosity combined with experimental data gave a simple static locus design procedure. A temperature profile was assumed for theoretical work but choice thereof was found to be not critical. Coefficients are defined in terms of a "zero" value and linear gradient. Using realistic criteria, measured coefficient variation was found to be significant at eccentricity ratios greater than 0.78. Theory adequately predicted most "zero" values but not gradients. It is concluded that improvement in the coefficient prediction will